A short history of Cahiers du cinéma - Bickerton, Emilie (London ; New York : Verso, 2011)
The crucible -- The yellow years -- Marble to modern chemistry -- Politicization -- Red notebooks -- The Daney years -- The mainstream -- After Cahiers -- Afterword -- Index of names and films cited.
Originally published: 2009.
Includes bibliographical references and index.
boek